The innovative diagnostic model facilitates the differentiation between non - tuberculous mycobacterial lung disease and pulmonary tuberculosis - Qiao, Mingkun; Li, Miao; Qi, Wenhui; Xu, Lei; Miao, Xiaohui; Cui, Chao (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivesTo construct a differential diagnostic model for Non-Tuberculous Mycobacterial Lung Disease (NTM-LD) and Pulmonary Tuberculosis Lung Disease (PTB-LD).MethodsRetrospective analysis of 300 NTM-LD and 300 PTB-LD patients (pathogen-confirmed) was performed. Patients were randomly split into training (2/3) and validation (1/3) sets. CT imaging, clinical data, and symptoms were analyzed. Logistic regression identified significant discriminative features, followed by random forest modeling to develop a diagnostic tool with web-based calculator. Model performance was validated using the independent validation set.ResultsUnivariate and multivariate analyses identified key discriminative factors (P<0.05): cough with sputum, hemoptysis, thin-walled cavities, centrilobular nodules, bronchiectasis, diabetes, and autoimmune diseases. The diagnostic model achieved 82.5% sensitivity and 85.5% specificity (ROC analysis), with validation showing 78% sensitivity and 85% specificity, confirming strong discriminative power and calibration.ConclusionsThe model constructed based on patients’ CT imaging, basic clinical data, and symptomatic signs demonstrates commendable performance in the differential diagnosis of NTM-LD and PTB-LD, offering a convenient and practical auxiliary tool for clinical practice.